City on trial: Examining the infrastructural turn in contemporary Filipino novels - Ramos, Jonah Leigh E. (Animo Repository, 2023)
Manila is a hotbed of infrastructure. As the favored scale of national representation in the highly globalized world, the city is made the project of both public and private entities seeking political and economic recognition in the global network. Experienced the most through its infrastructure, the city to the urban dweller has become the very physical networks mediating everyday life. This study posits that there has been an infrastructural turn in contemporary Filipino novels. A textual analysis of Glenn Diaz’s The Quiet Ones (2017) and Jun Cruz Reyes’s Ang Huling Dalagang Bukid at ang Authobiography na Mali: Isang Imbestigasyon (2011) in which infrastructure is read as both a concrete and a semiotic object highlights how profit-oriented infrastructures maintain colonial practices of slavery and exploitation. Framed particularly within Neferti Tadiar’s conceptual vocabulary from Remaindered Life (2022), the examined transportation and communication infrastructures point not only to the strong influence of the social and political elite in shaping urban space, but also to the liquid agency of the poor that makes them indispensable infrastructure of the city. Descriptions of the characters’ heightened senses toward, and even inevitable fusion with, infrastructure read furthermore as cry and demand for the shift to people-oriented infrastructure echoing Henri Lefebvre’s right to the city, for which this study finds an extended space in literature. Positioned as that other conceived space—following but also deviating from Lefebvrian terms—the contemporary Filipino novel allows opportunities to challenge, negotiate, and rethink the build of the city according to how it is experienced from the standpoint of dwellers rather than planners who continue to dominate the production of urban space.